Infant COVID-19 Infection: An Experience from Pediatric Intensive Care Unit of a Tertiary Care Dedicated Pediatric COVID Hospital - Sarkar, Mihir; Mahapatra, Manas Kumar; Ghosh, Sanajit; Chowdhoury, Satyabrata Roy; Kazi, Maha Ashraf; Datta, Kalpana (Journal of Pediatric Intensive Care, 2021)
This study aimed to assess different clinical, disease severity, laboratory, treatment, and outcome-related factors of COVID-19 positive infants admitted to a pediatric intensive care unit (PICU) and to compare these parameters with COVID-19 positive noninfants (1–12 years of age) who also required intensive care admission. This retrospective observational study was conducted in a PICU of a tertiary care, dedicated pediatric COVID facility. The clinical, epidemiological, laboratory parameters, and treatment outcomes of COVID-19 infected infants admitted to the PICU were recorded and analyzed. During comparison with the noninfant group, malignancy and coinfection with dengue and scrub typhus were excluded from both groups. A total 313 COVID-19 positive children aged from 1 month to 12 years old were admitted, of which 115 (36.7%) children required PICU admission. Infants constituted 37.4% of total PICU admissions. Most common symptoms were respiratory (83.7%) followed by fever (60.5%). Fifteen (34.9%) infants presented with shock. Ten infants (23.3%) had myocardial dysfunction. C-reactive protein (CRP) and ferritin were high in 60.5 and 16.7% infants, respectively. Fourteen infants needed invasive mechanical ventilation. Nine patients had acute respiratory distress syndrome (ARDS) and five had MIS-C. However, 53.5% infants had different comorbidities. Four infants died and all of them had severe comorbidities. Respiratory distress (p = 0.009), pediatric sequential organ failure assessment score (p = 0.032) and number of ARDS cases (p = 0.044) were significantly higher in infants than noninfants. Infants are one of the most vulnerable groups of children suffering from serious illness from COVID-19 infection requiring PICU admission due to predominantly respiratory involvement. Overall outcome was good among infants without significant comorbidity.
Keywords: infant; COVID-19; pediatric intensive care unit; acute respiratory distress syndrome